Correspondence between training load executed by volleyball players and the one observed by coaches - Rodriguez-Marroyo, J. A.; Medina, J.; Garcia-Lopez, J.; Garcia-Tormo, J. V.; Foster, C. (The Journal of Strength and Conditioning Research, 2014)
The main aim of this study was to compare the training load (TL) executed by volleyball players with that observed by coaches. Second, we analyzed the influence of the coaches' experience in the estimated TL. Twelve female volleyball players and 4 male coaches participated in this study. During a period of 15 weeks, physical (PT) and technical-tactical training sessions and matches were monitored. In each session, the session rating of perceived exertion (sRPE) was recorded to analyze the players' exercise intensity and TLRPE. Coaches were present in all sessions and rated their estimate of sRPE at the same time as the players to calculate the coaches' TLRPE. Both players' and coaches' mean sRPE (4.0 ± 1.1, 3.7 ± 1.1, and 3.8 ± 1.0 in players and expert and beginning coaches, respectively) and TLRPE (380.1 ± 106.8, 358.3 ± 110.5, and 359.7 ± 108.0 in players and expert and beginning coaches, respectively) were similar. However, a higher (p < 0.01) sRPE and TLRPE were observed in the players during PT. In general, the weekly TLRPE variation over the course of this study was similar in players and coaches. The players' sRPE and TLRPE were correlated (p < 0.01) with expert and beginner coaches' RPE (r = 0.70 and 0.72, respectively) and TLRPE (r = 0.75 and 0.76, respectively). In conclusion, the present findings show the correspondence between players' and coaches' sRPE and TLRPE regardless of their experience. Hence, coaches' TLRPE could be a useful and practical method to monitor and control the TL and other derived parameters in an easy way during volleyball.